2016
DOI: 10.1108/cms-01-2016-0022
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship among human resource flexibility, organizational innovation and adaptability culture

Abstract: Purpose Human resource (HR) flexibility is a firm-level capability that consists of employee skill flexibility, employee behavior flexibility, and HR practice flexibility. HR flexibility allows organizations to adapt and be responsive to changes in their environments. Findings from this paper indicate that if the organization is highly innovative and has flexible HR policies, then that influences organizational culture, risk-taking and experimentation within a firm. This paper has also revealed that process in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 82 publications
2
32
0
10
Order By: Relevance
“…Lúanaigh and Hughes [15] indicated that employees with proper autonomy of time would have higher satisfaction to further enhance the organizational performance. Do et al [13] stated that an enterprise need not pay extra welfare expenses for non-typical workers of temporary staff and outsourcers that it could control the costs and effectively promote the organizational performance. Way et al [16] proposed the maximal effect of human resource salary flexibility on employees' average monthly productivity that the higher salary flexibility would show better soft performance and higher average monthly production amount to effectively enhance organizational performance.…”
Section: Research Hypothesismentioning
confidence: 99%
“…Lúanaigh and Hughes [15] indicated that employees with proper autonomy of time would have higher satisfaction to further enhance the organizational performance. Do et al [13] stated that an enterprise need not pay extra welfare expenses for non-typical workers of temporary staff and outsourcers that it could control the costs and effectively promote the organizational performance. Way et al [16] proposed the maximal effect of human resource salary flexibility on employees' average monthly productivity that the higher salary flexibility would show better soft performance and higher average monthly production amount to effectively enhance organizational performance.…”
Section: Research Hypothesismentioning
confidence: 99%
“…Innovation and creativity are also essential so that the organization can win an increasingly stringent competition in the changing environment (Chow, 2017). An innovative organization is proven to maintain a competitive advantage (Johannessen & Skaalsvik, 2015;Ghosh, 2015) because it can respond faster to environmental changes (Do, Yeh, & Madsen, 2016). A key to the ability to create innovation to support the organization's performance is the support of the quality of human resources, which should be on the top priority (Rajiani & Norain, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The methods they used in doing these studies were structural equation models and multiple regression analysis. Organizational culture or atmosphere [10], leadership [9], organization-based self-esteem [24], and technical solution knowledge [25] are believed to be the factors that can promote employee creativity performance in most research. Because of the high uncertainty, external environment, and globally high competition, organizations need to have a dynamic ability to cope with fierce challenges to seek sustainable development.…”
Section: Human Resource Flexibility and Employee Creativitiy Performancementioning
confidence: 99%
“…Configuration 1 and configuration 2 have a stronger explanatory power than other paths, which implies that it is a critical consideration combination. Configuration 1 implies that when work values are unimportant in this particular path or employees with less distinct values, three dimensions of human resource flexibility will make joint efforts for creativity [9]. In particular, employee behavior flexibility is the core factor.…”
Section: Synergistic Effectsmentioning
confidence: 99%
See 1 more Smart Citation